Relationship Between Education and Hospital Visit - Kung, Chih-Chun (International Journal of Statistics in Medical Research, 2012)
The purpose of this paper is going to examine how the level of education affects their willingness to see a doctor and find whether the education is positive or negative correlated with the number of visiting a doctor based on 2 alternative hypotheses: (1) People have more years of education are more concerned about their health condition when they are ill, so the number of visiting a doctor should be positive correlated with their level of education, and (2) People with higher level of education pay more attention on their health condition by spending more time in exercise and therefore, this effort reflects that the number of visiting a doctor is negative correlated to their education level. The result shows if a person has more year of education, he is going to the hospital less frequently than the person with less education. One interesting finding is that the more exercise a person has, the more frequently he is going to the hospital because the risk of getting hurt by some equipment and joint problem may have significant contribution to the exercise. Some pitfalls of this study is we did not provide the alternative model for comparison such as binomial distribution model, and there is no marginal effect of each variable.